Implementation of Scratch Application to Improve Learning Outcomes and Student Motivation on Basic Programming Subjects - Lutfi Permatasari; Rosihan Ari Yuana; Dwi Maryono (Journal of Informatics and Vocational Education, 2019)
This study aims to improve learning outcomes and student motivation on Basic Programming Learning by utilizing the Scratch application. Research begins with identifying problems that occur in the classroom. Then designed an action to overcome it in an action cycle. In this study giving of the action takes place in two cycles. Each cycle consists of planning, implementation, observation, and reflection. In cycle 1, learning is implemented using problem-based learning model, while in cycle 2 using project-based learning. The technique of data collection is done through comprehension test, observation of learning activity, assignment of portfolio, and interview to students and related teacher. Data analysis was done using quantitative and qualitative interactive analysis techniques. The results showed that the use of Scratch application can improve learning outcomes and student motivation. This is indicated by the percentage of the student’s learning outcomes completeness by 25.7% in pre-cycle, 71.4% in cycle 1, and 94.3% in cycle 2. While the percentage of student motivation is 40.3% in pre-cycle, 75.1% in cycle 1, and 83.9% on cycle 2.